2012
DOI: 10.1371/journal.pone.0041126
|View full text |Cite|
|
Sign up to set email alerts
|

Pathological Steps of Cancer-Related Lymphedema: Histological Changes in the Collecting Lymphatic Vessels after Lymphadenectomy

Abstract: IntroductionTo date, an electron microscopy study of the collecting lymphatic vessels has not been conducted to examine the early stages of lymphedema. However, such histological studies could be useful for elucidating the mechanism of lymphedema onset. The aim of this study was to clarify the changes occurring in collecting lymphatic vessels after lymphadenectomy.MethodsThe study was conducted on 114 specimens from 37 patients who developed lymphedema of the lower limbs after receiving surgical treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
192
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(201 citation statements)
references
References 23 publications
7
192
1
1
Order By: Relevance
“…Interestingly, we did not find any correlation between dilatation of distal lymphatic vessels and duration of limb swelling. It is frequently considered that in longstanding lymphedema lymphatic dilatation is no more observed because of marked thickening of lymphatic wall; our study did not confirm this hypothesis (25).…”
Section: A Patientscontrasting
confidence: 98%
“…Interestingly, we did not find any correlation between dilatation of distal lymphatic vessels and duration of limb swelling. It is frequently considered that in longstanding lymphedema lymphatic dilatation is no more observed because of marked thickening of lymphatic wall; our study did not confirm this hypothesis (25).…”
Section: A Patientscontrasting
confidence: 98%
“…Previous studies have shown that clinical lymphedema results in progressive fibrosis of collecting lymphatic vessels, accumulation of α-SMA cells, and sclerosis of vessels with late-stage disease (13). Consistent with these reports, we noted progressive sclerosis and narrowing of the main hind limb collecting lymphatics as time progressed following DT administration (Figure 2, F and G).…”
Section: Dt Ablates Capillary and Collecting Lymphaticssupporting
confidence: 91%
“…In addition, since collecting lymphatic vessels at the wound area were obstructed and could not transport lymph downstream properly as evidenced by decreased lymphatic contractile function (Fig. 5(C)), the pressure in the collecting lymphatic vessels might increase gradually [19]. Thus, the conducting lymphatic vessels became dilated and tortuous (inset in Fig.…”
Section: Discussionmentioning
confidence: 99%